Pengaruh kesadaran, kecepatan transaksi, keamanan, manfaat yang dirasakan dengan mediasi persepsi kemudahan penggunaan terhadap adopsi m-banking BRI Makassar raya - Andi Dewi Mentari (Journal of Business & Banking)
Mobile banking, a banking facility, uses mobile communication tool such as mobile phones. They provide convenience for customers to perform banking transactions such as check balances, transfer between accounts and bill payments and know the history of transactions made by users. This study aims to analyze the infl uence of Awareness, Transaction Speed, Security, and Perceived Usefulness with Perceived Ease of Using Media for Adoption of m-banking in BRI Makassar Raya. The sample was taken from m-banking BRI customers in Makassar Raya. There were 100 respondents directly taken using purposive sampling technique. The data were analyzed using smartPLS programÂ (Partial Least Square) version 2.0. The results showed that awareness has a negative effect and not signifi cant towards BRI m-banking Adoption, Transaction Speed has a signifi cant and positive effect on BRI m-banking Adoption, Security has positive and signifi cant effect on BRI m-banking Adoption, Perceived Usefulness has no signifi cant effect to m -banking BRI, Perceived Usefulness has a signifi cant and negative effect on Perceived Ease of Use and Perceived Ease of Use has a signifi cant positive effect on m-banking Adoption.